A study on the non-compliance of peaceful assembly under the Peaceful Assembly Act 2012 / Sharizal Razali - Razali, Sharizal (2017)
This paper is a study on the exercise of the right to the peaceful assembly after the enactment of Peaceful Assembly Act 2012, particularly on the non-compliance of the organiser and participants towards the Act. The Act provides a specific procedure along with the restriction and conditions for the organiser and participants to exercise their right and to ensure the assembly is peaceful. However, the experience shows the failure of the organisers and the participants to comply with the provisions of the Act resulting lots of damaged and consequently affecting freedom of right of the third party. The scope of this dissertation analyses and compare the effectiveness of the laws in Malaysia and United Kingdom and incorporate the factors contribute to the non-compliance of the organiser and participants with the law. To balance between the social right to assembly peacefully and public order, recommendations are proposed to review Peaceful Assembly Act 2012 using Public Order Act 1986 the United Kingdom as the source of reference.